KS IOT Based Automation System to Prevent Crop Vandalization by Rain Water in Agricultural Regions - Saini, Kajal; Saini, Hunny; Gaur, Ankush Kumar (Jurnal Ilmu Komputer; Vol 14 No 2 (2021): Jurnal Ilmu KomputerDO - 10.24843/JIK.2021.v14.i02.p05, 2021)
India’s keystone is Agriculture. Around 70 percent of India’s revenue comes from Agriculture. Conversely the population of India amplifies each and every day which requires efficient and well planned decision making techniques for the production of crops. In this research paper we find the intensification of the structures which prevent destruction of crops due to uneven and heavy rainfall. The goal is achieved by the concept of Embedded System design using IOT technology. This is done automatically without any human interference. Here we first identifies the water level in the agriculture field during rainfall by using water level sensors , if the water level exceeds there limit that will cause spoilage of crop then the device are automatically cover the agriculture field. It also identifies the temperature of the crops by using temperature sensor during the sunny days, if the heat causes spoilage of crops due to intensive sun rays then the device will automatically covers the agriculture field. After covering the agriculture field it will send the alert message using GSM module to the farmer and simultaneously the water of rain is collected through piles that will be reuse later for irrigation. To achieve this we use microcontroller , Solar panels, GSM module, DC motor, sensors, Switched-mode power supply (SMPS), Rechargeable battery